Beyond PARP1: The Potential of Other Members of the Poly (ADP-Ribose) Polymerase Family in DNA Repair and Cancer Therapeutics - Richard, Iain A.; Burgess, Joshua T.; O’Byrne, Kenneth J.; Bolderson, Emma (Frontiers in Cell and Developmental Biology, 2022)
The proteins within the Poly-ADP Ribose Polymerase (PARP) family encompass a diverse and integral set of cellular functions. PARP1 and PARP2 have been extensively studied for their roles in DNA repair and as targets for cancer therapeutics. Several PARP inhibitors (PARPi) have been approved for clinical use, however, while their efficacy is promising, tumours readily develop PARPi resistance. Many other members of the PARP protein family share catalytic domain homology with PARP1/2, however, these proteins are comparatively understudied, particularly in the context of DNA damage repair and tumourigenesis. This review explores the functions of PARP4,6-16 and discusses the current knowledge of the potential roles these proteins may play in DNA damage repair and as targets for cancer therapeutics.